Development of wireless electronic nose and using of remote monitoring - HU Ying; WANG Jun (浙江大学学报. 农业与生命科学版, 2013)
The electronic nose system is the simulation of mammalian olfactory system, to identify or classify the fruits according to odor. The traditional electronic noses commonly use the expensive card for data acquisition, which leads to the increased cost, meanwhile the existence of wired access need high maintenance cost and the extensible system defects and mobility are poor, especially it can’t detect in real-time in harmful environment. To solve the above problems, a kind of electronic nose system was put forward which has eight wireless data transmission based on ZigBee, and when the monitoring nodes have been arranged, nobody is needed to visit the scene.The system combined the latest wireless sensor networks. The past research about it was focused on little road data or information transmission control, but rarely on multi-channel data transmission. With sensors and synchronous transport signal increasing, we should pay attention to data accuracy and packet loss rate. This system used the CC2530 chip for 8-way wireless data transmission. The system included a monitoring node of the data acquisition, a coordinator node for organization and data aggregation of ZigBee and remote management system for data storage and processing. The system can set multiple monitoring nodes and monitor the object of several places through the network at the same time which is convenient and cost saving.Firstly, a wireless electronic nose system was designed based on ZigBee technology to detect the level of fruit freshness and food spoilage. The system included a monitoring node of the data acquisition, a coordinator node for organization and data aggregation of ZigBee and remote management system for data storage and processing. The hardware and software components of the system were designed. The hardware part included selection of the components, structure and principle of graph nodes, in order to ensure the realization of the system. It focused on the design of data acquisition and processing module, power module, the interface circuit design, antenna impedance matching design of wireless communication module. The software introduces the structure of Z-Stack plate on the transplant, CC2530 data acquisition, AD (Analog to digital) conversion process and the development of the applications for the eight channel data acquisition and transmission, to ensure the accuracy of data transmission.Secondly, the communication quality of the system was evaluated and applied to detect the plum fruits. Plum samples were tested in 5 days (twice per day) at a certain temperature and humidity, using principal component analysis which can probably show the plum change trend, and the use of BP neural network can accurately determine the growth stage of each sample. The SVM analysis had a good recognition rate using eigenvector analysis after PCA. The experiments showed that the wireless electronic nose could be used for remote monitoring of fresh fruits.In all, wireless electronic nose system based on ZigBee is cost saving, convenient and flexible, also has good scalability and mobility with a good application prospect. At the same time, selecting the appropriate pattern recognition algorithm can make the system more accurate.